An enhancement of using CBIR in image mosaic generation - Maniego, Jennelyn D. and Piclac, Jewel C. 4 0 16; 5
u
Undergraduate Thesis:(Bachelor of Science in Computer Studies major in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2